أثر التسهيلات الائتمانية الممنوحة من البنوك الإسلامية الأردنية في عرض النقد: دراسة تحليلية للفترة من 2011-2020 م. - Hdaib, Salman Ghazi; Abu Bakir, Sahar Mohd (جامعة العلوم التطبيقية الخاصة - عمادة البحث العلمي والدراسات العليا, 2023)
هدفت الدراسة إلى قياس أثر تكامل سلسلة التزويد بأبعادها في الأداء التنظيمي باستخدام بطاقة الأداء المتوازن بأبعاده في شركات الصناعات الدوائية الأردنية: الدور المعدل لنظام الإنتاج في الوقت المحدد. استخدم المنهج الوصفي لتحقيق أهداف الدراسة،، تكون مجتمع الدراسة من جميع شركات الصناعات الدوائية في الأردن والتي بلغ عددها (20) شركة. وتكونت وحدة المعاينة من (273) فردا شملتهم الدراسة جميعا. ولجمع البيانات والمعلومات الضرورية تم الاعتماد على الاستبانة، وباستخدام برنامج التحليل الإحصائيSPSS أظهرت النتائج وجود أثر ذو دلالة إحصائية عند مستوى دلالة (α ≤ 0.05) لتكامل سلسلة التزويد بأبعاده (التكامل مع الموردين، والتكامل مع الموزعين) في الأداء التنظيمي باستخدام بطاقة الأداء المتوازن بأبعاده (التعلم والنمو، العمليات الداخلية، ورضا العملاء) في شركات الصناعات الدوائية الأردنية، ووجود أثر ذو دلاله إحصائية عند مستوى دلالة (α ≤ 0.05) لنظام الإنتاج في الوقت المحدد في تعديل أثر تكامل سلسلة التزويد بأبعاده مجتمعة في الأداء التنظيمي بأبعاده مجتمعه في شركات الصناعات الدوائية الأردنية. وأوصت الدراسة بضرورة التأكيد على أهمية استمرار شركات الصناعات الدوائية الأردنية بعلاقات التكامل والتعاون مع أعضاء سلسلة التزويد، وكذلك الاستمرار في تطبيق نظام الإنتاج في الوقت المحدد وتوفير كافة متطلبات تطبيقه بنجاح. The purpose of this study is to investigate the impact of Supply Chain Integration in terms of (integration with suppliers, integration with distributors) on Organizational Performance using the balanced scorecard dimensions (learning and growth, internal processes, and customers’ satisfaction) in Jordanian Pharmaceutical Manufacturing Companies: The moderating role of the Just in Time Production System. The quantitative descriptive analytical approach used to achieve the objectives of the study. The study population consisted of all the (20) Jordanian pharmaceutical Manufacturing Companies operating in Jordan. The analysis and sampling unit consisted of (273) member totally surveyed. The questionnaire was used to collect the needed data. Based on the Statistical Package for Social Sciences (SPSS) the results of the statistical analysis showed that there is a statistically significant impact of (integration with suppliers, and integration with distributors) on organizational performance using the balanced scorecard dimensions (learning and growth, internal operations, and customer satisfaction) in the Jordanian pharmaceutical manufacturing companies at level (α ≤ 0.05). And there is a statistically significant impact of Just in Time Production System (JIT) in modifying the impact of supply chain integration on the performance of the Jordanian pharmaceutical manufacturing companies at the level (α ≤ 0.05). The study recommends that the Jordanian pharmaceutical manufacturing companies should continue building cooperation and integration relationships with supply chain members (suppliers and distributors), and to keep on implementing Just in Time Production System and guarantee that all the requirements for successful application of the system are available.
Keywords: المؤسسات الصناعية -- الأداء التنظيمي -- الصناعات الدوائية -- الأردن